Pengaruh Technical Sales Skill dan Non Technical Sales Skill terhadap Kinerja Tenaga Penjualan melalui Kepercayaan Konsumen sebagai Variabel Intervening (Universitas Negeri Semarang, 2015)
The purpose of this research is to explain technical sales skill, non-technical sales skill give influence toward sales performance through consumer confidence has a role as intervening variable. The sampling uses incidental sampling technique. The numbers of respondents are 116 respondents. The methods used to collect the data are questionnaire method, interview method and observation method. Data analysis used in this research is path analysis with IBM SPSS Statistics 20 program. The result of this research shows that consumer confidence variable has a role as intervening variable between technical sales skill and non-technical sales skill toward sales performance. The conclusion of this research is consumer confidence has a role as intervening variable between technical sales skill, and non technical sales skill, toward sales performance.